Samorząd terytorialny miasta Kalisza. Doświadczenia minionego dwudziestolecia - ŻMURKIEWICZ, Agnieszka (Przegląd Politologiczny, 2018)
The reinstatement of local government at the level of the district in Poland in 1990 has resulted in the actual empowerment of local communities, while the local governments have become able to define the goals of local policy that are in line with the expectations of local communities. The local government of Kalisz has taken advantage of the new opportunities to improve the living conditions and standard of living of its citizens since it was instituted. Over the years, due to changes in the political system, related to the establishment of counties, the local government of Kalisz has received new operating opportunities, implementing projects at the level of both districts and counties. The political transformation was complemented by the changes in the election principles of the executive, which has significantly improved the efficiency and effectiveness of the President of Kalisz. The activities of local government have been concentrated on the increasing of social integration by means of taking maximum advantage of local assets and potential. In order to achieve these goals promotional instruments have been employed to encourage foreign investors to investment in Kalisz. A significant part of the local government’s activities concern its longstanding international cooperation with towns in Western, as well as Central and Eastern Europe.